Analysis of Faults in the Mechanical Part of Railway Weight Checking Wagons (Eurasian Journal of Engineering and Technology, 2022)
In this article, the problem is relevant, such as extending the service life of 640-VPV weighing wagons operated on the territory of the Republic of Uzbekistan. The analysis of the technical condition of the weighing wagon metal structures revealed defects that could affect their service life